Impact of heatwaves and cold spells on the morbidity of respiratory diseases: A case study in Lanzhou, China. (February 2020) - Xu, Ge; Chen, Ling; Chen, Yi; Wang, Tao; Shen, Fei-Han; Wang, Ku; Jin, Shao-Fei
Abstract: More than four hundred million people suffer from respiratory diseases each year. Respiratory diseases are associated with a large disease burden. Heatwaves and cold spells, the two most common extreme weather events, have been shown to have crucial negative effects on the prevalence of respiratory diseases. However, impacts of extreme weather on the prevalence of respiratory diseases has been largely overlooked in western China, where more intense and frequent extreme temperature events have been occurring over the past decades. This research gap will obtain an attribution bias in the effects of extreme weather events on the prevalence of respiratory diseases. Therefore, in this study, we analyzed the impact of heatwaves and cold spells on the morbidity of respiratory diseases using a distributed lag nonlinear model with daily disease cases from 2013 to 2016 in Lanzhou, one of the largest cities in western China. A reverse U-shaped relationship depicted the relationship between temperature and the morbidity of respiratory diseases. The highest relative risk was found at 2.6 °C by 1.15 (95% confidence interval: 1.09–1.21). Furthermore, we found a significant decrease in the relative risk for heatwaves and a significant increase in the relative risk of cold spells when the temperature exceeded the corresponding threshold by 1 °C. Heatwaves and cold spells play harvest effects on the morbidity of respiratory diseases. Our study suggest that the relative risk of respiratory diseases will increase as the climate warms in the future, and thus a preventive system is needed for individuals and medical policy-makers. Highlights: A reverse U shape relationship between temperature and respiratory disease exists in Lanzhou. Extreme temperature events exhibit a harvest effect on the respiratory disease. The greatest relative risk of respiratory disease was found at 2.6 °C.